2014
DOI: 10.1111/ger.12143
|View full text |Cite
|
Sign up to set email alerts
|

Diagnoses of 964 oral biopsies from people aged over 50 years in Karnataka State, India

Abstract: The study provides valuable information about major oral pathologies in our scenario that contribute to significant morbidity and mortality among the geriatric population. It also sheds light about the diseases that need to be targeted in future Indian public health policies and initiatives for geriatric care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 11 publications
(40 reference statements)
8
20
1
Order By: Relevance
“…Thus, histopathological studies have the advantage of being more accurate since this type of analysis is considered the gold standard for the diagnosis of many diseases. [7][8][9][10][11][12] In the present study, the prevalence of oral lesions among older adults was 16% when calculated considering patients of all ages. Although variable prevalence rates have been reported, our results are similar to the 9-14% found in other studies.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, histopathological studies have the advantage of being more accurate since this type of analysis is considered the gold standard for the diagnosis of many diseases. [7][8][9][10][11][12] In the present study, the prevalence of oral lesions among older adults was 16% when calculated considering patients of all ages. Although variable prevalence rates have been reported, our results are similar to the 9-14% found in other studies.…”
Section: Discussionmentioning
confidence: 89%
“…However, retrospective studies assessing data from services have showed that, usually, old individuals are affected by at least one lesion. When the frequency of the OMLs was computed, the types of lesions most commonly observed among older people included inflammatory/reactive lesions, malignant neoplasms (10,11), infectious diseases, and potentially malignant disorders (5).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9]15 In the elderly patients, the most common tongue lesion in the present was squamous cell carcinoma which is in accordance with previous studies on geriatric oral lesions based on histopathological examination. [10][11][12][13]…”
Section: Discussionmentioning
confidence: 99%
“…There have been several epidemiological studies on oral mucosal lesions and tongue lesions constitute a considerable proportion of the oral lesions, [5][6][7][8][9][10][11][12][13] but information specific to the tongue lesions is difficult or impossible to extract from those studies. Prevalence of tongue lesions varies in different parts of the world due to demographic and/or geographic differences of the sample studied, as well as differences in the diagnostic criteria, study methodology, and sampling process 14 ; hence conducting studies on the prevalence of tongue lesions in different geographic regions seems imperative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation